2021
DOI: 10.3390/d13100499
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Capital Value of the Seagrass Posidonia oceanica in the North-Western Mediterranean

Abstract: Posidonia oceanica is an endemic Mediterranean seagrass used as a ‘biological quality element’ in monitoring programmes of the EU Water Framework Directive, providing information about coastal ecosystems status. The regression of P. oceanica meadows caused a growing interest among policy makers to assess the value of seagrasses and to increase their protection. An evaluation of P. oceanica meadows located in the Ligurian-Provençal basin (NW Mediterranean) through a biophysical approach is here developed. Six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…Seagrasses-marine flowering plants forming submerged meadows up to 40 m deep-and especially the endemic and most common species in the basin Posidonia oceanica-have been the bioengineers of this structurally complex seascape framework for millennia (Arnaud-Haond et al, 2012). Covering less than 2% of the total Mediterranean seabed, the P. oceanica seagrass meadows provide a plethora of ecosystem services valued between 57,000 to 184,000 €/ ha/year (Paoli et al, 2018;Rigo et al, 2021) and are globally significant carbon sinks, with greater organic carbon density than the observed one in estuarine mangroves, peatlands or tropical forests (IUCN, 2021). The large efficiency of such vegetated coastal ecosystems in absorbing and storing carbon, and thus reducing atmospheric carbon dioxide concentration, has led to initiatives to include them in climate change mitigation strategies like REDD+ (Reducing Emissions from Deforestation and Forest Degradation) (Duarte et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Seagrasses-marine flowering plants forming submerged meadows up to 40 m deep-and especially the endemic and most common species in the basin Posidonia oceanica-have been the bioengineers of this structurally complex seascape framework for millennia (Arnaud-Haond et al, 2012). Covering less than 2% of the total Mediterranean seabed, the P. oceanica seagrass meadows provide a plethora of ecosystem services valued between 57,000 to 184,000 €/ ha/year (Paoli et al, 2018;Rigo et al, 2021) and are globally significant carbon sinks, with greater organic carbon density than the observed one in estuarine mangroves, peatlands or tropical forests (IUCN, 2021). The large efficiency of such vegetated coastal ecosystems in absorbing and storing carbon, and thus reducing atmospheric carbon dioxide concentration, has led to initiatives to include them in climate change mitigation strategies like REDD+ (Reducing Emissions from Deforestation and Forest Degradation) (Duarte et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that predators have a positive impact on their prey, directly or indirectly (see the Healthy Herd Hypothesis) [40]. In a way, the modern concept of ecosystem services (e.g., [46][47][48][49][50][51][52]) fits into the logic of the human-centred approach to nature, though it is much more complex and integrated. The integrated management of man and nature throughout the application of the theories of natural capital and ecosystem services could even be considered as a fourth level of management.…”
Section: The Three Steps In the Approaches To Biodiversity Management 21 The Human-centred Approachmentioning
confidence: 99%
“…The area covered by P. oceanica in coastal areas is estimated between 22 000 and 23 000 km 2 (Pergent-Martini et al, 2020;Traganos et al, 2022), making it one of the most important carbon sinks of the Mediterranean Sea (Pergent et al, 2012). Despite providing crucial ecosystem services (Vassallo et al, 2013;Bryan et al, 2016;Rigo et al, 2021), there is no doubt that P. oceanica has strongly declined in Mediterranean notably near the most anthropized areas like major harbours (e.g., Barcelona, Marseille, Genoa, Naples) (Boudouresque et al, 2021;Telesca et al, 2015). This global regression is mainly related to anthropogenic pressure (e.g.…”
Section: Introductionmentioning
confidence: 99%